Acute Kidney Injury Associated With Urinary Stone Disease in Children and Young Adults Presenting to a Pediatric Emergency Department - Farris, Nicholas; Raina, Rupesh; Tibrewal, Abhishek; Brown, Miraides; Colvis, Maria; Schwaderer, Andrew; Kusumi, Kirsten (Frontiers in Pediatrics, 2020)
Background: Acute Kidney Injury (AKI) due to urinary stone disease (USD) is rare in adults; AKI rates in children with USD may be higher, and emerging data links stones to Chronic Kidney Disease (CKD) development in adults. Methods: Retrospective analysis of USD patients at a single pediatric hospital system’s emergency department (ED). Patients were initially identified by USD ICD codes; USD was then confirmed by imaging or physician documentation; patients had to have baseline creatinine (Cr) and Cr in the ED for comparison to be included. AKI was defined by Kidney Disease: Improving Global Outcomes (KDIGO), Acute Kidney Injury Network (AKIN) and Pediatric Risk Injury Failure End Stage (pRIFLE). Results: 589 total visits; 264/589 (45%) had data to evaluate for AKI; 23% AKI(+) and 77% AKI(-). pRIFLE was most common (82%); 18% were only positive by AKIN/KDIGO. AKI(+) were more likely to be younger (16.7 vs 17.4 years, p=0.046) and present with vomiting (OR(95%CI): 2.4 (1.4-4.3), p=0.002); also the proportion of AKI(+) was significantly higher in <18 years vs. ≥18 years (26.9% vs. 15.5%, p=0.032, OR (95%CI): 2.0 (1.1 - 3.9)). Urinary Tract Infection (UTI) and obstruction rates were similar between groups. AKI(+) patients had a significant OR <1 suggesting less risk of receiving NSAIDs, however, 51% of them did receive NSAIDs during their ED encounter. AKI(+) patients were more likely to require admission to the hospital (53% vs 32%, p=0.001). Conclusion: We have demonstrated a novel association between USD induced renal colic and AKI in a group of young adults and children. AKI(+) patients were younger and were more likely to present with vomiting. AKI(+) patients did not have higher rates of obstruction or UTI. 51% of AKI(+) received NSAIDs.